重型湿式制动车桥制动能回收系统及控制策略的研究 - 罗天洪; 左磊; 李富盈; 胡启国 (Jixie Chuandong, 2014)
Taking the working situation of heavy wet brake axle during aperiod of time as the research object.The allocation strategy of brake pressure in front and rear axle,brake energy recovery control,and battery quick charging and protection strategy of the wet drive axle type braking energy recycling equipment are analyzed in detail.Contrast with the structure of some recovery unit,a heavy axle of wet braking energy recycling equipment integrated with the aspects of assembly difficulty,structure size,difficulty of maintenance,unit weight and recovery efficiency that have improved significantly is introduced.And on this basis,the quantity of recycling energy of the system energy recycling equipment is analyzed and calculated,by calculating the system can recycle the braking energy,prove that the recycling control strategy is effective.